Dismissal of KPK Employees from Legal Positivism and Alternative Solutions - Dominikus Dalu Sogen; Dewa Ayu Putri Asvini; Detty Kristiana Widayat (Iapa Proceedings Conference, 2021)
Studying the philosophy of law means studying various schools of law. Amongst the variety of legal theories, there are adherents of legal positivism or the positive legal theory postulated by John Austin (a philosopher whose thoughts on law are outlined in a work entitled The Province of Jurisprudence Determined 1832). Are Austin's thoughts still relevant for the practice of law inthe modern era, considering that law is made for the public interest? Is it appropriate for the law to be made by authorities (superior) to bind subordinates (inferior), whereas the people are only in a position to obey the law? In a functioning democracy public participation is important in decision-making by the elected legislators. Presumably, law is not made arbitrarily or unilaterally, but it is supposed to take into account the interest of the public or the interest of the groups it is designed to address. A prominent example currently in the public spotlight isthe dismissal of 57 Corruption Eradication Commission (KPK) employees due to their stated ineligibility following their failure to pass the National Insight Test Assessment. For this matter, a judicial review (JR) has been requested from the Constitutional Court and the Supreme Court who in the meantime have published their decisions. In addition, there have been recommendations from the National Human Rights Commission (Komnas HAM) and the Indonesian Ombudsman regarding the occurrence of human rights violations and maladministration in the transfer of KPK employees to ASN. Where JR's decision by the two judicial institutions is different from what is recommended by Human Right Commission and the Indonesian Ombudsman. Here it can be seen that there are differences in the application of the law with the positive law that applies and is detrimental to the rights of KPK employees.